Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s10840-022-01352-4
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radioablation therapy as an immediate and early term antiarrhythmic palliative therapeutic choice in patients with refractory ventricular tachycardia

Abstract: Background Stereotactic body radioablation therapy (SBRT) has recently been introduced with the ability to provide ablative energy noninvasively to arrhythmogenic substrate while reducing damage to normal cardiac tissue nearby and minimizing patients’ procedural risk. There is still debate regarding whether SBRT has a predominant effect in the early or late period after the procedure. We sought to assess the time course of SBRT’s efficacy as well as the value of using a blanking period following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…I look forward to in vivo data from this group, as do Tschabrunn and Frankel, who nicely comment on this study in their editorial [15]. Lastly, Aras and colleagues add to the growing body of literature on VT stereotactic body radiation therapy (SBRT) with their single-center study of 8 patients in whom suppression of VT seemed most prominent in the first 3 months post-SBRT, with questionable long-term efficacy [16].…”
Section: ) What If I Cannot Get Into the Pericardial Space?mentioning
confidence: 92%
“…I look forward to in vivo data from this group, as do Tschabrunn and Frankel, who nicely comment on this study in their editorial [15]. Lastly, Aras and colleagues add to the growing body of literature on VT stereotactic body radiation therapy (SBRT) with their single-center study of 8 patients in whom suppression of VT seemed most prominent in the first 3 months post-SBRT, with questionable long-term efficacy [16].…”
Section: ) What If I Cannot Get Into the Pericardial Space?mentioning
confidence: 92%
“…Solving the Reach Problem: A Review of Present and Future Approaches for Addressing Ventricular Arrhythmias Arising from Deep Substrate Lower VA burden and ICD therapy 63 Improved quality of life in multiple small studies [63][64][65] Non-invasive mapping and Lower procedure time Modification of operator strategy in 43% of cases 45 High correlation of between image identified substrate and critical isthmus/LAVA 46 Imaging processing performed at external site Lead time may be required Advances in ablation catheter technologies include the use of higher impedance irrigation, changes in the energy source used for ablation, and pre-ablation cardiac imaging which has been introduced to improve the efficacy of catheter ablation for VT. 9,10…”
Section: New Technologies For Ablation Of Vasmentioning
confidence: 99%
“…In a retrospective study (n=8), the highest arrhythmic benefit in terms of VT burden and ICD interventions was in 2 weeks to 3 months after SBRT, perhaps due to transcription and eventual replacement of gap junctions over time after SBRT. 63 The authors surmised SBRT should be considered as a bailout strategy or bridge therapy until heart transplantation in refractory cases. In a study of 10 patients with repeated ICD therapies and refractory to standard treatment, SBRT demonstrated a reduction in VT duration and a trend for reduction in ICD shocks.…”
Section: Stereotactic Body Radiation Therapymentioning
confidence: 99%
“…18,[49][50][51] Although some teams subsequently reported less marked improvements, cardiac SBRT has emerged as a promising ablative therapy with a growing number of case series reporting the effectiveness of the technique in reducing the burden or eliminating VAs refractory to conventional therapies. 17,20,[52][53][54][55][56][57][58][59][60][61][62] Regarding quality of life, significant improvement in perceived health change and social functioning has been highlighted after cardiac SBRT for refractory VAs. 18,49,62 Short-term safety profile of cardiac SBRT also appears favorable, although long-term data are needed.…”
Section: Cardiac Sbrt For Refractory Vasmentioning
confidence: 99%
“…After the initial case reports in human in 2014 and 2015, the ENCORE‐V and ENCORE‐VT trials demonstrated the short‐term safety and efficacy of the technique for reducing VA recurrences (more than 90% of patients experiencing significant VA burden reduction) 18,49–51 . Although some teams subsequently reported less marked improvements, cardiac SBRT has emerged as a promising ablative therapy with a growing number of case series reporting the effectiveness of the technique in reducing the burden or eliminating VAs refractory to conventional therapies 17,20,52–62 . Regarding quality of life, significant improvement in perceived health change and social functioning has been highlighted after cardiac SBRT for refractory VAs 18,49,62 .…”
Section: Cardiac Sbrt For Refractory Vasmentioning
confidence: 99%